Interferon Potentiates Toll-Like Receptor-Induced Prostaglandin D2 Production through Positive Feedback Regulation between Signal Transducer and Activators of Transcription 1 and Reactive Oxygen Species - Kim, Ji-Yun; Choi, Go-Eun; Yoo, Hyun Ju; Kim, Hun Sik (Frontiers in Immunology, 2017)
Prostaglandin D2 (PGD2) is a potent lipid mediator that controls inflammation and its dysregulation has been implicated in diverse inflammatory disorders. Despite significant progress made on the role of PGD2 as a key regulator of immune responses, the molecular mechanism underlying PGD2 production remains unclear, especially upon challenge with different and multiple inflammatory stimuli. Interferons (IFNs) potentiate macrophage activation and act in concert with exogenous inflammatory mediators such as TLR ligands to amplify inflammatory responses. Recent study indicates an enhancing effect of IFN-gamma on LPS-induced PGD2 production, pointing to a role of IFNs in PGD2 regulation. Here, we demonstrate that TLR-induced PGD2 production by macrophages was significantly potentiated by signaling common to IFN-beta and IFN-gamma in a STAT1-dependent mechanism. Such a potentiation by IFNs was also observed for PGE2 production despite a differential regulation of PGD synthase (PGDS) and PGES isoform mediating PGD2 and PGE2 production under inflammatory conditions. Mechanistic study revealed that the generation of intracellular reactive oxygen species (ROS) is remarkably potentiated by IFNs and required for PGD2 production but is nullified by STAT1 deficiency. Conversely, the regulation of STAT1 level and activity by IFNs was largely dependent on ROS levels. Using a model of zymosan-induced peritonitis, the relevance of this finding in vivo was supported by marked inhibition of PGD2 and ROS produced in peritoneal exudate cells by STAT1 deficiency. Collectively, our findings suggest that IFNs, although not activating on their own, are potent amplifier of TLR-induced PGD2 production via a positive-feedback regulation between STAT1 and ROS.